2006
DOI: 10.1002/ajmg.b.30398
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin receptor HTR1B: Gene polymorphisms in attention deficit hyperactivity disorder

Abstract: Serotonin plays an essential role in cognition, locomotor activity, and the regulation of sleep, pain, mood, and aggression. Polymorphisms of the HTR1B gene have been implicated in a variety of psychiatric disorders including attention deficit hyperactivity disorder (ADHD) and obsessive-compulsive disorder (OCD). The objectives of this study were to: (i) expand our original investigation of the relationship between the HTR1B receptor gene and attention deficit/ hyperactivity and; (ii) to investigate a possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Genetic studies have shown an association between variation in the HTR1B gene and a number of phenotypes, including attention deficit hyperactivity disorder, [28][29][30] obsessive compulsive disorder, 31 antisocial alcoholism, 32 substance dependence and major depression. 33 However, many of the association findings have been inconsistent, [34][35][36] and this may be due to an incomplete awareness of the extent of functional variation within the HTR1B gene. Another difficulty in determining the contribution of the HTR1B gene to behavior is the lack of an appropriate behavioral measure.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies have shown an association between variation in the HTR1B gene and a number of phenotypes, including attention deficit hyperactivity disorder, [28][29][30] obsessive compulsive disorder, 31 antisocial alcoholism, 32 substance dependence and major depression. 33 However, many of the association findings have been inconsistent, [34][35][36] and this may be due to an incomplete awareness of the extent of functional variation within the HTR1B gene. Another difficulty in determining the contribution of the HTR1B gene to behavior is the lack of an appropriate behavioral measure.…”
Section: Discussionmentioning
confidence: 99%
“…For the meta-analysis of rs6296, data were available from four TDT (Brookes et al 2006a;Ickowicz et al 2007;Li et al 2005;Smoller et al 2006) and Wve Case-Control/ HHRR (Bobb et al 2005;Guan et al 2008;Hawi et al 2002;Heiser et al 2007;Ribases et al 2009) studies. Based on the initial study , the 'G' allele was designated as the 'risk' allele.…”
Section: Serotonin 1b Receptor (Htr1b; 5ht1b)mentioning
confidence: 99%
“…In family-based studies Kent et al, reported significant (p=0.04) association of the T689 allele with ADHD cases (Kent et al 2002) which has not been confirmed by subsequent familybased (Banerjee et al, 2009, Heiser et al, 2007, Wigg et al, 2006, Xu et al, 2005 and case-control haploblock comprising rs6296, rs6297, rs130060, rs6298, rs130058 and rs11568817 is linked with the inattentive subtype of ADHD. The findings were not, however, replicated in a subsequent study (Ickowicz et al, 2007).…”
Section: G689tmentioning
confidence: 63%